(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The author examines don Milani’s “Letter to a professor” and “Letter to judges” from the point of view of his own experience, first as a student and then as a teacher, posing the problem of their relevance. From this analysis emerges on the one hand the impossibility of reducing its meaning to the denunciation of the blockage of the social elevator and of the need for a didactic renewal, on the other hand to emphasize what the two texts pose, i.e., the problem of how to get out of the condition of subject to become citizen-sovereign.